Mechanistic Impact of Zinc Deficiency in Human Development - Hussain, Azhar; Jiang, Wenting; Wang, Xiukang; Shahid, Shumaila; Saba, Noreena; Ahmad, Maqshoof; Dar, Abubakar; Masood, Syed Usama; Imran, Muhammad; Mustafa, Adnan (Frontiers in Nutrition, 2022)
Zinc (Zn) deficiency in humans is an emerging global health issue affecting approximately 2 billion people across the globe. The situation prevails due to intake of Zn deficient grains and vegetables worldwide. Clinical identification of Zn deficiency in humans remains problematic because the symptoms does not appear until impair the vital organs including gastrointestinal track, central nervous system, immune system, skeletal and nervous system. Lower Zn body levels are also responsible for multiple physiological disorders like apoptosis, organs destruction, deoxyribonucleic acid (DNA) injuries and oxidative damage to the cellular components through reactive oxygen species (ROS). The oxidative damage causes chronic inflammation lead towards several chronic diseases like heart diseases, cancers, alcohol-related malady, muscular contraction, and neuro-pathogenesis. The present review focused on the physiological and growth-related changes in humans under Zn deficient conditions, mechanisms adopted by human body under Zn deficiency for proper functioning of the body systems and the importance of nutritional and nutraceutical approaches to overcome Zn deficiency in humans and conclude that the biofortified food is a best source of Zn as compared to the chemical supplementation to avoid their negative impacts on human.